Dynamic Oligopoly Pricing: Evidence from the Airline Industry - Caspar Siegert; Robert Ulbricht (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We explore how pricing dynamics in the European airline industry vary with the competitive environment. Our results highlight substantial variations in pricing dynamics that are consistent with a theory of intertemporal price discrimination. First, the rate at which prices increase towards the scheduled travel date is decreasing in competition, supporting the idea that competition restrains the ability of airlines to price-discriminate. Second, the sensitivity to competition is substantially increasing in the heterogeneity of the customer base, reflecting further that restraints on price discrimination are only relevant if there is initial scope for price discrimination. These patterns are quantitatively important, explaining about 83 percent of the total within-flight price dispersion, and explaining 17 percent of the observed cross-market variation of pricing dynamics.
urn:nbn:de:bvb:19-epub-20866-8
Keywords: D43; D92; L11; L93; 330; Airline industry; capacity constraints; dynamic oligopoly pricing; intertemporal price dispersion; price discrimination